The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7759/cureus.31289
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Evaluation of Podcast Learning, Retention, and Electroencephalographically Measured Attention in Medical Trainees

Abstract: Introduction: Podcasts have become popular among medical trainees. However, it is unclear how well learners retain information from podcasts compared to traditional educational modalities, and whether multitasking affects the learner's ability to pay attention and learn. This study attempted to examine the effectiveness of podcast learning by using electroencephalography (EEG) to measure learner attention, in addition to test performance, task load, and preferences.Methods: The study used a repeated measures d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a randomized study including 130 medical students, audio podcasts were shown to achieve better learning outcomes as compared to textbook reading, related to orthopedic diseases 13 . A recent study by Wolpaw et al confirmed that audio podcast listening may enhance learning and retention of knowledge compared to textbook reading 3 . Interestingly, in this study, there were no differences in learning when comparing audio podcast listening during exercise on a treadmill to audio podcast listening in a seated position.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…In a randomized study including 130 medical students, audio podcasts were shown to achieve better learning outcomes as compared to textbook reading, related to orthopedic diseases 13 . A recent study by Wolpaw et al confirmed that audio podcast listening may enhance learning and retention of knowledge compared to textbook reading 3 . Interestingly, in this study, there were no differences in learning when comparing audio podcast listening during exercise on a treadmill to audio podcast listening in a seated position.…”
Section: Discussionmentioning
confidence: 48%
“…13 A recent study by Wolpaw et al confirmed that audio podcast listening may enhance learning and retention of knowledge compared to textbook reading. 3 Interestingly, in this study, there were no differences in learning when comparing audio podcast listening during exercise on a treadmill to audio podcast listening in a seated position. The potential learning benefits of audio podcast use compared to textbook reading may however be limited to certain topics, since there were no differences between the learning conditions for one out of three studied topics (statistics).…”
Section: Audio Podcast-and Procedural Video-based Learning In the Con...mentioning
confidence: 47%
See 2 more Smart Citations
“…9 In a study examining effectiveness of podcast learning that used electroencephalography (EEG) to measure learner attention, podcast listening was preferred to reading in self-reported satisfaction ratings and produced a higher level of learning gain. 10 Content and style appear important, and although structured podcasts based on curricula may have benefit for learning, narrative podcasts are also an engaging form of obtaining information, 11 with active aversion to episodes that are simply recorded lectures. 12 Podcasts offer the convenience of learning on the go.…”
mentioning
confidence: 99%